Hypoallergen Peanut Lines Identified Through Large-Scale Phenotyping of Global Diversity Panel: Providing Hope Toward Addressing One of the Major Global Food Safety Concerns - Pandey, Arun K.; Sudini, Hari K.; Upadhyaya, Hari D.; Varshney, Rajeev K.; Pandey, Manish K. (Frontiers in Genetics, 2019)
Peanut allergy is one of the serious health concern and affects more than 1% of the world’s population mainly in Americas, Australia, and Europe. Peanut allergy is sometimes life-threatening and adversely affect the life quality of allergic individuals and their families. Consumption of hypoallergen peanuts is the best solution, however, not much effort has been made in this direction for identifying or developing hypoallergen peanut varieties. A highly diverse peanut germplasm panel was phenotyped using a recently developed monoclonal antibody-based ELISA protocol to quantify five major allergens. Results revealed a wide phenotypic variation for all the five allergens studied i.e., Ara h 1 (4–36,833 µg/g), Ara h 2 (41–77,041 µg/g), Ara h 3 (22–106,765 µg/g), Ara h 6 (829–103,892 µg/g), and Ara h 8 (0.01–70.12 µg/g). The hypoallergen peanut genotypes with low levels of allergen proteins for Ara h 1 (4 µg/g), Ara h 2 (41 µg/g), Ara h 3 (22 µg/g), Ara h 6 (829 µg/g), and Ara h 8 (0.01 µg/g) have paved the way for their use in breeding and genomics studies. In addition, these hypoallergen peanut genotypes are available for use in cultivation and industry, thus opened up new vistas for fighting against peanut allergy problem across the world.